Oral and Maxillofacial Surgery for the Clinician - Bonanthaya, Krishnamurthy; Panneerselvam, Elavenil; Manuel, Suvy; Kumar, Vinay V.; Rai, Anshul (Springer Nature, 2021)
This is an open access book with CC BY 4.0 license. This comprehensive open access textbook provides a comprehensive coverage of principles and practice of oral and maxillofacial surgery. With a range of topics starting from routine dentoalveolar surgery to advanced and complex surgical procedures, this volume is a meaningful combination of text and illustrations including clinical photos, radiographs, and videos. It provides guidance on evidence-based practices in context to existing protocols, guidelines and recommendations to help readers deal with most clinical scenarios in their daily surgical work. This multidisciplinary textbook is meant for postgraduate trainees, young practicing oral surgeons and experienced clinicians, as well as those preparing for university and board certification exams. It also aids in decision-making, the implementation of treatment plans and the management of complications that may arise. This book is an initiative of Association of Oral and Maxillofacial Surgeons of India (AOMSI) to its commitment to academic medicine. As part of this commitment, this textbook is in open access to help ensure widest possible dissemination to readers across the world. ; Open access Unique presentation with contents divided into color-coded core competency gradations Covers all aspects of oral and maxillofacial surgery Supplemented with videos of all commonly carried out procedures as operative video Every chapter or topic concludes with "future perspective" and addresses cutting edge advances in each area Every topic has a pull out box that provides the most relevant systematic reviews/ key articles to every topic